Prevalence of Sinonasal Cancer in Dr. Sardjito General Hospital Yogyakarta in The Period between January 2017 and December 2022 - Indrasari, Sagung Rai; Herdini, Camelia; Yudistira, Danu; Mary, Cynthia (Indonesian Journal of Cancer, 2024)
Background: Sinonasal cancer is considered a rare disease and data concerning the disease in Indonesia still requires extensive research. This study aimed to describe the factors that contribute to the incidence and outcome of sinonasal cancer. Methods: This was a descriptive study conducted at the Department of Otorhinolaryngology, Head and Neck Surgery, Dr. Sardjito General Hospital Yogyakarta between January 2017 and December 2022. Data regarding histopathological type, sex, age, location of tumor, presence of metabolic syndrome, staging, treatment, overall survival, and cancer recurrence were extracted from the patient’s medical records. All patients diagnosed with sinonasal cancer within the period were included in the study. Results: A total of 117 patients were included in this study ranging from 11 to 85 years of age and averaging 54,5 years. Most patients were diagnosed within the age range of 51 – 60 years. SCC was found to be the most common and it was more prevalent in males than in females. More patients were found to have suprastructure tumors. Most patients were not recorded to have metabolic syndrome. The majority of patients were diagnosed in the late stage of sinonasal cancer and overall survival for most cases was death. More patients received 2 or less therapy, followed by patients who received all 3 types of treatment. Recurrency was found in only 1,7% of all cases. Conclusion: Several conditions can affect the incidence and outcome of sinonasal cancer which include sex, age of diagnosis, presence of risk factors (e.g. metabolic syndrome), location of tumor, staging, treatment, recurrence, and the histopathological type.